2014
DOI: 10.19177/jrd.v2e1201458-68
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of condylar translation in hyperdivergent and hypodivergent patients: a pilot study

Abstract: Introduction: The present pilot study aims to compare the condylar translation between patients with hyperdivergent and hypodivergent facial pattern. Methods: after analysis of photographs and cephalometric data, sample obtained was divided into two groups: hyperdivergent (n = 12) and hypodivergent (n = 12). For evaluation of condylar translation, temporomandibular joint planigraphys with maximum mouth opening and maximum intercuspal were performed. Subsequently, the tracing of maximum mouth opening in the art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A significant and higher condylar translation has been noted in hyperdivergent patients compared to the hypodivergent group in the studies conducted by Giradot Jr et al and Poluha et al 22,23 Other authors such as Akan et al 24 and Erverdi et al 25 also added a posterior bite block for posterior intrusion and demonstrated significant mandibular counterclockwise rotation, by stimulating muscular response. However, they have used cephalometrics alone to substantiate their results.…”
Section: Discussionmentioning
confidence: 96%
“…A significant and higher condylar translation has been noted in hyperdivergent patients compared to the hypodivergent group in the studies conducted by Giradot Jr et al and Poluha et al 22,23 Other authors such as Akan et al 24 and Erverdi et al 25 also added a posterior bite block for posterior intrusion and demonstrated significant mandibular counterclockwise rotation, by stimulating muscular response. However, they have used cephalometrics alone to substantiate their results.…”
Section: Discussionmentioning
confidence: 96%